Photobiomodulation therapy in the post-operative management of puerperal mastitis-associated breast abscess (Research, Society and Development, 2022)
Although phototherapies have been used to manage nipple lesions and pain in breastfeeding women, there is no information on alternative therapies treating puerperal mastitis-associated breast abscess. The current study aimed to present a case in which adjuvant photobiomodulation therapy was used for a breast abscess developed as a complication of puerperal mastitis. Despite receiving antibiotic therapy, exudate drainage, surgical cleaning, and drain placement, after 11 days, the patient was still experiencing pain and there were marked inflammation signs on the region. Fifteen sessions of photobiomodulation therapy were then proposed. Pain relief was achieved after 3 laser sessions and wound healing after 15 laser sessions. According to the current case, photobiomodulation therapy seems to be a valuable adjuvant therapeutic modality for puerperal mastitis-associated breast abscess.